Mapping Digital Competence: Students' Maker Literacies in a School's Makerspace - Kumpulainen, Kristiina; Kajamaa, Anu; Leskinen, Jasmiina; Byman, Jenny; Renlund, Jenny (Frontiers in Education, 2020)
This study investigates and maps students’ maker literacies as they relate to digital competence. The study builds on sociocultural theorizing and on the scholarship of digital literacy that defines maker literacies as social practices that entail making and remaking artifacts and texts using various materials and technologies. Through a detailed multimodal analysis of video data from an ethnographic case study of students’ (N:11) interaction in an elementary school’s makerspace in Finland, our study presents and applies a framework of analysis for maker literacies and discusses how the school’s makerspace enhanced the students’ digital competence across operational, cultural, and critical dimensions. The study shows how the makerspace context afforded the students ample opportunities to engage in the operational dimension of maker literacies. However, there was less engagement in cultural and critical literacies. The implications of these findings for students’ digital competence in makerspaces are discussed.